Summary - St John, Susan (Victoria University of Wellington Law Review, 2003)
The Accident Compensation Scheme was introduced in New Zealand as a form of social insurance. The issue quickly became whether ACC should embody private insurance principles. This article explores this very issue and other future challenges in ACC going forward, including determining what types of injuries ACC should cover, the role of welfare economics, and the tension between the no-fault concept with ACC’s emphasis on cost/price signals.